Effectiveness of refractive error correction for people with oculocutaneous albinism in Nepal - Bhari, Arjun M; Bajracharya, Kabindra; Thapa, Hari B; Gautam, Maria; Pandey, Araniko; Bassett, Ken (Asian Journal of Medical Sciences, 2017)
Background: Albinism is commonly associated with high refractive errors, but some clinicians are reluctant to prescribe glasses because reduced vision persists due to additional non-refractive visual problems. Aims and Objective: The purpose of this study was to evaluate the effectiveness of glasses in people with oculocutaneous albinism in Nepal. Materials and Methods: People with Oculocutaneous albinism (OCA) were prospectively examined through an outreach program of Lumbini Eye Institute, Nepal. Glasses were prescribed to determine the objective improvement in visual acuity (VA) and strabismus. Compliance with spectacles wear was assessed by telephone contact after 3 weeks and categorized as excellent: >75% of awake hours; good: 50–75% of awake hours; fair: 26–50% of awake hours and poor: <25%. Results: Thirty one people (65% male) mean age 18 years (range: 3 to 50) with OCA were examined. Mean refractive correction was –0.40±4.3 diopters spherical equivalents (range: −11.0 to +7.0 D). Mean visual acuity at distance was 0.9±0.28(6/50) corrected and 1.150.31(5/60) uncorrected (P = 0.000) in 62 eyes. Mean neat VA was1.74±0.89M corrected and 2.06±1.20M uncorrected (P = 0.004). Forty eight per cent (15 people) had fusion with or without glasses and one had fusion only with glasses. Compliance was excellent in 52% (16), fair in 26% (8), good in 12% (4), and poor in 10% (3). Conclusion: Providing eye glasses resulted in a clinically and functionally significant improvement in visual acuity and function in people with OCA. Asian Journal of Medical Sciences Vol.8(6) 2017 30-34